EVOLUTION OF EXCLUSIVE BREASTFEEDING IN THE FIRST 15 YEARS OF THE 21TH CENTURY: A STUDY IN THE MUNICIPALITY OF MACAÉ, RIO DE JANEIRO, BRAZIL - Alice Bouskelá; Jane de Carlos Santana Capelli; Camilla Medeiros Macedo da Rocha; Flavia Farias Lima; Naiara Sperandio; Vânia de Matos Fonseca (Universidade do Estado do Rio de Janeiro, 2019)
This study aims to investigate the prevalence rate and the temporal trend of exclusive breastfeeding (EBF) in infants under four months of age attended at the Basic Health Units of Family Health Strategies (UBS/ESF) in Macaé, between 2001 and 2015. A time series study was conducted to evaluate the evolution of the prevalence rates of EBF at four months, considering the given period, with descriptive character and use of secondary data, DATASUS - Database of the Unified Health System via Basic Care Information System - SIAB/SUS. The EBF trend analysis was performed using the Jointpoint Regression Program software for Windows version 4.5.0.1. A total of 56,454 records were analyzed. For the total number of children studied, EBF presented a statistically significant increase from 47.2% to 69.0% between 2001 and 2004. For the following period, the practice of EBF varied until the prevalence of 73.5% in 2015, with a maximum value of 76.8% in 2013, but these variations did not show statistical significance in this time interval, with an average annual rate of 71.4% in the last ten years. An optimistic evolution dynamic regarding EBF has been established for more than a decade in the city of Rio de Janeiro, confirming that investment in policies and in various promotion, protection and support actions can have a positive impact and should remain for the continuous and necessary increase in breastfeeding. DOI: 10.12957/demetra.2019.43562